Displacement of the nervous system through articular movement by ultrasound. Bibliographic review - Munné, Carles; Pedret, Carles (Apunts : medicina de l'esport, 2018)
The nervous system has the capacity to adapt to the mechanical forces of tension, compression and shearing to which it is exposed in daily movements. Reduction of nerve slide may alter its function by increasing neural tension, which may have an adverse effect, contributing to the onset of pain. The objective of the study was to review the current literature regarding the movement of the nervous system and how to measure it. To do this, a search was undertaken in Pubmed and PEDro of articles where neural displacement is measured by the “frame-by-frame cross correlation system” technique. Twenty studies were selected: 14 measured displacement in healthy subjects, and 6 compared some form of peripheral neuropathy. The results show that the peripheral nervous system is displaced during the different movements of body segments to adapt to the space through which it runs, although there is no significant difference in displacement between healthy people and patients with nerve involvement. El sistema nervioso tiene la capacidad de adaptarse a las fuerzas mecánicas de tensión, compresión y cizallamiento a las que se ve expuesto en los movimientos diarios. La reducción del deslizamiento del nervio puede alterar su función por el incremento de la tensión neural, pudiendo afectar negativamente y contribuir a la aparición de dolor. El objetivo del estudio es revisar la bibliografía actual respecto al desplazamiento del sistema nervioso y cómo medirlo. Para ello se realiza una búsqueda en Pubmed y PEDro de artículos donde se mida el desplazamiento neural mediante la técnica de «frame-by-frame cross correlation system». Se seleccionan 20 estudios: 14 de ellos miden el desplazamiento en personas sanas y 6 comparan con algún tipo de neuropatía periférica. Los resultados muestran la capacidad de movimiento del sistema nervioso periférico durante los diferentes movimientos de segmentos corporales para adaptarse al espacio por donde discurre, aunque no hay una diferencia significativa de desplazamiento entre personas sanas y pacientes con afectación nerviosa.